2022
DOI: 10.1590/1980-220x-reeusp-2022-0058en
|View full text |Cite
|
Sign up to set email alerts
|

Project-based learning in remote teaching for undergraduate nursing students

Abstract: Objective: To report the experience of using the Project-Based Learning methodology, in emergency remote teaching, with undergraduate nursing students. Method: The study was carried out in the course “Educational Actions in Nursing Practice”, developed remotely in 2020, during the pandemic caused by the new coronavirus, in the Bachelor’s and Licanciate Degrees in Nursing at a public university in the state of São Paulo. The course used Project-Based Learning through the following phases: anchoring; driving qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…While in this study the main results were improved interdisciplinary and learning, a study conducted in nursing students in Brazil found that PBL associated with the use of new information technologies allows the achievement of learning objectives, increasing motivation and autonomy, favoring meaningful learning (Pascon et al, 2022). Another study conducted in Chile shows that PBL is a good teaching methodology for school children to solve problems in the real world, encouraging a participatory role in the learning process (Borroni et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…While in this study the main results were improved interdisciplinary and learning, a study conducted in nursing students in Brazil found that PBL associated with the use of new information technologies allows the achievement of learning objectives, increasing motivation and autonomy, favoring meaningful learning (Pascon et al, 2022). Another study conducted in Chile shows that PBL is a good teaching methodology for school children to solve problems in the real world, encouraging a participatory role in the learning process (Borroni et al, 2021).…”
Section: Discussionmentioning
confidence: 60%
“…Para tanto, a atividade que previa a imersão nas realidades regionais se ancorava no estudo de grupos vulnerabilizados, o que potencializou o trabalho em equipe e a interação, essenciais para treinar habilidades de liderança e de comunicação (4,5) . Nesse sentido, percebeu-se como as estratégias mediadoras foram essenciais para excitar tais quesitos (6,7) .…”
Section: Discussionunclassified
“…Para alcançar essas competências e seus resultados, as estratégias mediadoras são as apresentações visuais e escritas, revelando constructos sobre equidade que dialogam sobre as práxis do enfermeiro (7,8) . Nota-se que os desfechos colocam o aluno como protagonista da aprendizagem, considerando sua realidade, inclusive por meio de análises coletivas, de problemas emergentes e de estímulos para investigação, usando recursos de E-learning que possibilitem práticas colaborativas, as quais permitem a construção de conhecimentos pelo estímulo entre pares e por meio da realidade do aluno, observadas as necessidades do SUS (9) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Figure 1 depicts the Gold Standard PjBL model, which highlights both the design elements and teaching practices that are key in PjBL (BIE, n.d.). In nursing education, PjBL has been linked to improved learning outcomes as well as critical thinking and problem-solving skills (Arif & Putri, 2022;Bassi, 2011;Daley & Sciegaj, 2021;Hanklang & Sivasan, 2019;Koo et al, 2022;Pascon et al, 2022;Sung & Wu, 2018;Wahyuningsih et al, 2020).…”
Section: Contextmentioning
confidence: 99%